A Comparison of CPR on a Hard Surface Compared to CPR on a Mattress - Kara Stout; Lee Doernte; Riley Phipps (International Journal of First Aid Education)
Background: High-quality cardiopulmonary resuscitation (CPR) is critical for improving survival outcomes in cardiac arrest patients. However, the compliance of surfaces like hospital mattresses and household beds may compromise CPR effectiveness by reducing compression depth and increasing rescuer fatigue. Objective: To investigate the metabolic and performance differences of CPR performed on a hard surface versus a standard hospital mattress and discuss implications for lay responders performing CPR in out-of-hospital settings. Methods: A randomized cross-over study involving 34 trained participants assessed CPR quality and rescuer physiological responses on two surfaces: a hard floor and a hospital mattress. Participants performed continuous chest compressions on a manikin for 24 minutes under each condition. Measurements included heart rate (HR), oxygen consumption (VO₂), ventilatory equivalent for oxygen (Ve/VO₂), fraction of expired oxygen (FeO₂), compression depth and rate, and ratings of perceived exertion (RPE). Results: Performing CPR on a mattress significantly increased HR (mean difference: -4.1 ± 9.8 bpm; p = 0.020) and VO₂ (mean difference: -14.8 ± 7.2 mL/kg/min; p < 0.001) compared to the hard surface. Compression depth was significantly reduced on the mattress (mean difference: 3.4 ± 3.5 mm; p < 0.001). Ve/VO₂ difference increased (mean difference: -3.3 ± 8.3; p = 0.025), and FeO₂ difference decreased (mean difference: 0.7 ± 1.3%; p < 0.001) on the mattress, indicating increased metabolic demands and reduced ventilatory efficiency. RPE scores were higher on the mattress at both midpoint (mean difference: -0.5 ± 1.3; p = 0.006) and completion (mean difference: -0.2 ± 1.0; p < 0.001). No significant difference in compression rate was observed (p = 0.843). Conclusions: CPR performed on a compliant surface like a hospital mattress or household bed increases the rescuer's metabolic demands and reduces compression depth, potentially compromising resuscitation effectiveness. Strategies to mitigate the effects of surface compliance, such as moving the patient to a hard surface or using backboards, should be considered to improve CPR quality in both clinical and out-of-hospital settings.